Horseback fighting in Pietro del Monte’s Collectanea (1509): from training to the reality of pitched battle - Bas Pierre-Henry (Acta Periodica Duellatorum)
The Italian Pietro del Monte left us a wonderful work on the martial arts of the late XVth century. Writing on weapons, gear, and fighting techniques, he gives special attention to horses and horseback fighting. In this succinct article, the goal is to present the two different types of cavalry that are covered directly or indirectly by Monte and to show his wide experience in the field, which led him to suggest some pragmatic techniques and not just write a book showing a wide range of technical and tactical possibilities.